Towards optical data transmission for high energy physics using silicon photonics. (1st May 2022) - Prousalidi, T.; Bulling, A.; Court, M.; Detraz, S.; Lalović, M.; Marcon, L.; Olanterä, L.; Orfanelli, S.; Sandven, U.; Scarcella, C.; Sigaud, C.; Soós, C.; et al.
Abstract: Future upgrades of CERN experiments will require low power optical data links to support ever-increasing data-rates at ever-higher radiation levels. Silicon photonics is a CMOS optoelectronic technology compatible with these requirements. We present the results of an optical transceiver proof of concept based on a silicon photonics integrated circuit coupled to existing radiation tolerant electronic ASICs.